Comparative Analysis of Earthing Resistance on Rod and Plate Electrodes for Improvement of Earthing Resistance Values - Yoga Tri Nugraha; Lidya Rahmani Laia; Baharuddin Ismail (Journal of Electronics, Telecommunication, Electrical, and Physics Science, 2022)
The availability of a grounding system must have the smallest grounding resistance value. To obtain a grounding resistance value with a certain value is influenced by several factors such as: the shape of the grounding system, soil type, soil temperature, soil moisture, electrode diameter, soil electrolyte content and others. the ground surface, and in the form of plates or plates, all of which are designed to reduce grounding resistance. From the results of measurements and calculations, the value of grounding resistance is obtained from the measurement results above, indicating the depth of the grounding electrode is 1.5 m deep, at this depth the value of grounding resistance is 0.98 Î©. The rod electrode, while the plate electrode is 1.6 Î©. and the calculation of the ground resistance using Dwight's formula, the average value of the rod electrode is 0.9 Î© and the plate, the average value is 0.5 Î©. There is a difference between the results of calculations and measurements this is due to differences in the perception of the type of electrode used. It is < 1 Î© meets the requirements of PUIL, 2000, for wet and moist soil types.